Strengthening Community Economy Inclusively through Literacy for Prosperity : National Library of Indonesia’s Role to Support Sustainable Development Goals (SDGs) - Reza Mahdi (The Journal of Indonesia Sustainable Development Planning, 2020)
The term literacy continues to evolve from time to time according to the conditions of a society. At first, UNESCO in 1997 concluded that literacy is the ability to identify, understand, interpret, communicate, and count using printed or other materials, but the meaning of literacy is much more than that, which in the end a literate community can produce something that is beneficial to individuals or society. Therefore, the prosperity of a society can be seen from the number of literate people. National Library of Indonesia has recorded it in the concept of literacy for prosperity in the Social Inclusion-Based Library Transformation program. One of the programs carried out is for the prosperity of the literacy-based economic community that also aims to support SDGs. Until now, the National Library of Indonesia has succeeded in bringing about a positive impact on the community's economy with the concept of as well as support for SDGs. In the future, there are still many things that must be researched by the National Library of the Republic of Indonesia regarding literacy for inclusive prosperity.